Analysis of taxonomic distinctness and priority conservation areas as a basis for heritage enhancement of floristic diversity: the case of the ‘hotspot’ of the islands of Numidia (North-eastern Algeria) - Hamel, Tarek; Hidalgo Triana, Noelia; Meddad-Hamza, Amel; Boulemtafes, Amir; Souilah, Nabila; de Bélair, Gérard; Salvo Tierra, Ángel Enrique (Mediterranean Botany, 2023)
The identification of priority conservation areas (PCA) plays an important role in biodiversity conservation, but uncertainties create challenges for conservation planning. The objective was to test a method based on 'taxonomic distinctness' (TD) and to identify PCA to quantify the heritage value of a territory and establish the most appropriate conservation measures. The researchers performed a systematic and phytogeographical analysis of ten islands in northeastern Algeria, a biological hotspot with heterogeneous ecosystem types and subject to socio-economic pressures. The biological diversity represented by 223 species in these environments reflects a high rate of endemicity (13%).